Pengaruh Efek Sosial dan Ekonomi Terhadap Kemiskinan di Nusa Tenggara Timur - Marsela, Tasya (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2024)
Development in Indonesia aims to create a just, prosperous, and independent society, with the government adopting the Sustainable Development Goals (SDGs) to ensure equitable national development. This research uses a quantitative method. The findings on the success of the Sustainable Development Goals Without Poverty in East Nusa Tenggara conclude that mobile phones play an important role in reducing poverty by providing access to new opportunities. Smoking does not significantly affect poverty; however, increasing the gross enrollment rate has proven effective in reducing poverty. Income levels also play a significant role. Therefore, coordinated efforts are needed to address poverty by focusing on these factors